Rac1 modulates mammalian lung branching morphogenesis in part through canonical Wnt signaling - Danopoulos, Soula (Am J Physiol Lung Cell Mol Physiol, 2016)
Lung branching morphogenesis relies on a number of factors, including proper epithelial cell proliferation and differentiation, cell polarity, and migration. Rac1, a small Rho GTPase, orchestrates a number of these cellular processes, including cell proliferation and differentiation, cellular alignment, and polarization. Furthermore, Rac1 modulates both noncanonical and canonical Wnt signaling, important pathways in lung branching morphogenesis. Culture of embryonic mouse lung explants in the presence of the Rac1 inhibitor (NSC23766) resulted in a dose-dependent decrease in branching. Increased cell death and BrdU uptake were notably seen in the mesenchyme, while no direct effect on the epithelium was observed. Moreover, vasculogenesis was impaired following Rac1 inhibition as shown by decreased Vegfa expression and impaired LacZ staining in Flk1-Lacz reporter mice. Rac1 inhibition decreased Fgf10 expression in conjunction with many of its associated factors. Moreover, using the reporter lines TOPGAL and Axin2-LacZ, there was an evident decrease in canonical Wnt signaling in the explants treated with the Rac1 inhibitor. Activation of canonical Wnt pathway using WNT3a or WNT7b only partially rescued the branching inhibition. Moreover, these results were validated on human explants, where Rac1 inhibition resulted in impaired branching and decreased AXIN2 and FGFR2b expression. We therefore conclude that Rac1 regulates lung branching morphogenesis, in part through canonical Wnt signaling. However, the exact mechanisms by which Rac1 interacts with canonical Wnt in human and mouse lung requires further investigation.